The Structure of Data in Medical Records - Astrid, M. van Ginneken (Yearbook of Medical Informatics, 1995)
With the growing complexity of health care, patient data are more and more in demand for purposes such as research, education, postmarketing surveillance, quality assessment, and outcome analysis. Many of these purposes require patient data to be available in a structured, electronic format. Despite the rapid advances in computer technology, which allow patient data to be organized, analyzed, and shared, the majority of physicians still use paper medical records. Apparently, most physicians still perceive the paper record as being more suitable for their task than present day computerized versions. Both the shortcomings and the strengths of paper medical records have been identified and it proves difficult to design a computerized medical record that exploits the strengths of computers without loosing the advantages of the paper chart. The structure of patient data is an area of high interest, since structure determines how physicians, other health care workers, and patients may benefit from these data. An overview of research efforts in structuring patient data will offer insight in the problems that still impede a widespread use of the computerized patient record in clinical practice.
Keywords: Computer-based Patient Records; Problem-Oriented Medical Records; Natural Language Processing; Structured Data Entry